Implementation of an Advance Directive Protocol among Hospitalized Patients - Byrd, Lila (My University, 2018)
Background. Medical advancements have progressed considerably in recent decades, highlighting the necessity of advance care planning (ACP). Advance directives (ADs) help honor and promote patient preference, quality of life (QOL), and reduced health care costs. While Centers for Medicare and Medicaid Services (CMS) requires institutions to screen and educate all patients during admission on ADs, there is not a standardized process for agencies to follow. Problem. Prior to project implementation, in a hospital network in southeastern North Carolina, initiatives were being done in the ambulatory setting to increase AD completion and having them located in the EHR. The aim of this project was to increase the number of ADs correctly located in the EHR on a progressive care unit (PCU) at a hospital in southeastern North Carolina. Methodology. A DNP-led quality improvement project was implemented to increase the number of ADs located in the EHR. The intervention included the creation of an ACP navigator tab in the EHR to provide a standard location for AD admission screening and links to ADs scanned in to the EHR. Data collected included the number of patients with ADs and the number of them correctly located in the EHR. Data was gathered eight-weeks prior to implementation of the ACP navigator and eight-weeks post intervention. Results. Before the ACP navigator, 26.2 percent of patients with ADs had them on file in the EHR. After the ACP navigator, 35.7 percent of patients with ADs had them correctly located in the EHR. Conclusions. ADs are essential to patients receiving care consistent with their wishes. With the growing use of the EHR, ADs have the capability of being available across care settings. The addition of an ACP navigator in the EHR aids in standardizing the location of ADs and ensuring patients wishes are followed.